PENERAPAN MEDIA PUZZLE UNTUK PEMAHAMAN MATERI DAUR HIDUP HEWAN DI SEKOLAH DASAR DENGAN PENDEKATAN SAINS-EDUTAINMENT - Safrina Junita; Haris Munandar (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
This research was motivated by observations in several elementary schools in Aceh Besar and Banda Aceh that the fourth grade students of elementary school still had a low ability to describe and explain the steps in the life cycle of animals. In addition, the teacher also does not use the media in the learning process of animal life cycle concepts. The purpose of this study is to apply puzzle learning media to students' understanding of animal life cycle material. The results of the study indicate that the results of the application of media puzzles on the subject of animal life cycle can increase the understanding of fourth grade students of SD 69 on the material. This is evidenced by the acquisition of the value of student learning outcomes in the posttest with the percentage of 87.5% of students included in the category